(untitled) (International Journal of Geoscience, Engineering and Technology, 2024)
Population growth, industrialization, and the expansion of agriculture in the 20th century worsened the scarcity and degradation of water resources, and for this reason, water management became part of political and socioeconomic debates. The present work aimed to characterize the Three Hearts fluviometric station, located in the municipality of Três Corações, and demarcate the drainage area of the Rio Grande sub-basin, which is part of the greater Paraná River basin. Through remote sensing tools, it was possible to extract information such as elevation model, drainage networks, transversal profiles, basin slope, use of Thiessen Polygons, and flow calculation in geotechnology software (QGis version 2.18), which became important for these types of analyses is evident. This type of study is fundamental because this is the territorial unit for the purposes of planning and managing water resources, which made it possible to characterize the Three Hearts fluviometric station, located in the Municipality of Três Corações.